2022
DOI: 10.1177/13591045221095300
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions in childhood cancer survivor and caregivers’ dyads

Abstract: Surviving childhood cancer is a difficult experience for children and their caregivers, it can produce long-term emotional distress. Illness perceptions refer to the way people understand the different aspects related to illness from their individual and collective experiences. Objective: to compare the illness perceptions of adolescent childhood cancer survivors and their caregivers and examine the relationship between illness perception of childhood cancer survivors, their caregivers, and sociodemographic, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a study examining the perception of mothers with children diagnosed with cancer, mothers perceived their children as less independent compared to healthy children, and more often displayed an emotionally ambivalent attitude towards their children than that of their counterparts with healthy children [ 22 ]. In a study on illness perception focused on childhood cancer survivors and their caregivers, caregivers perceived the illness to be more severe compared to the perception of cancer survivors themselves; the study recommend the need for expert intervention to bridge this gap in perception [ 23 ]. Moreover, they emphasized that these perception gap findings would provide valuable insights into the understanding of relationships with other mental health variables, including psychological trauma, fatigue, and the process of returning to school and work [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study examining the perception of mothers with children diagnosed with cancer, mothers perceived their children as less independent compared to healthy children, and more often displayed an emotionally ambivalent attitude towards their children than that of their counterparts with healthy children [ 22 ]. In a study on illness perception focused on childhood cancer survivors and their caregivers, caregivers perceived the illness to be more severe compared to the perception of cancer survivors themselves; the study recommend the need for expert intervention to bridge this gap in perception [ 23 ]. Moreover, they emphasized that these perception gap findings would provide valuable insights into the understanding of relationships with other mental health variables, including psychological trauma, fatigue, and the process of returning to school and work [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on illness perception focused on childhood cancer survivors and their caregivers, caregivers perceived the illness to be more severe compared to the perception of cancer survivors themselves; the study recommend the need for expert intervention to bridge this gap in perception [ 23 ]. Moreover, they emphasized that these perception gap findings would provide valuable insights into the understanding of relationships with other mental health variables, including psychological trauma, fatigue, and the process of returning to school and work [ 23 ]. They also stressed the importance of monitoring these differences in perception between survivors and caregivers to gain better understanding of the interconnections among these variables [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This understanding of the disease is effective in the behavior, the person’s adaptation to the disease, the management of the disease by the person, and the treatment of the disease. Studies on disease perception have shown that disease perception includes five dimensions, including recognition of symptoms, duration of the disease, cause of the disease, outcome of the disease, and its curability [ 12 ]. Disease perception is related to some of the results of the illness, including care behaviors and individual management, which can be attributed to the influence of the patient’s beliefs on his behavior.…”
Section: Introductionmentioning
confidence: 99%